Assessment of the levels of serum Hsp 70 and ghrelin in children with simple febrile convulsions - Kilic, Mehmet; Gunduzalp, Mehmet; Taskin, Erdal; Aydin, Suleyman; Serin, Hepsen M. (Edizioni Minerva Medica, 2016)
BACKGROUND: In this study we aimed to evaluate the serum levels of Heat-shock protein (Hsp) 70 and acylated and desacylated ghrelin in patients suffering from a simple febrile convulsion. METHODS: This cross-sectional study included patients who were diagnosed with a simple febrile convulsion, afebrile tonic-clonic epileptic seizure and upper respiratory tract infection when admitted to our hospital. All patients were aged between six months and 60 months. Patients enrolled in this study were divided into five groups. Group I: patients with a simple febrile convulsion and body temperature of 38 degrees C to 39 degrees C; group II: patients with a simple febrile convulsion and body temperature of 39.1 degrees C to 41 degrees C; group III: patients with primary generalised tonic clonic seizure and normal body temperature; group IV: patients with upper respiratory infection without convulsion and a body temperature of 38 degrees C to 39 degrees C; and group V: patients with upper respiratory infection without convulsion and a body temperature of 39.1 degrees C to 41 degrees C. The control group included healthy children who were followed up in the healthy children polyclinic. Serum levels of Hsp70 and acylated and des-acylated ghrelin were studied from the blood samples collected from the patients and control group. RESULTS: Serum levels of Hsp70 were higher in the febrile convulsion (groups I, II) and epileptic convulsion and infection (groups IV, V) groups than in the controls (P<0.0001). Moreover, serum levels of acylated and desacylated ghrelin were higher in the simple febrile convulsion (groups I and II) and epileptic convulsion and infection (groups IV and V) groups than in the control (P<0.05). CONCLUSIONS: We demonstrated that serum levels of Hsp70 and acylated and desacylated ghrelin increased in patients with a simple febrile convulsion.
Keywords: Seizures, Febrile; HSP70; Heat-Shock Proteins; Fever; Ghrelin; Child